RELASI NEGARA DAN MASYARAKAT DI ROTE - Therik, Wilson M.A. (KRITIS, 2016)
This article abstracted from dissertation entitled “State and Society’s Relation in Rote”. This article discusses the relation between the state and society in Rote Island. Rote Island (Rote Ndao District) consisted of 19 Kingdom (Nusak) with different culture, language, and customs on each Nusak. Nusak divides the government structure into 3 (three) functions: First is the executive institution body which run custom law, second is the legislative body which make custom law, and third is the judicative body which monitoring custom law. By this condition, Nusak is considered as Ethnic State. From this explanation, Indonesia should be seen as nations state, not as a nation state.